STRATEGI PRODUKSI PROGRAM TALKSHOW UMPAT BETAKUN DI SALURAN DAKWAH ISLAMIC CENTER KALIMANTAN TIMUR DALAM MENYAJIKAN PESAN KOMUNIKASI - Indriani Lubis, Hafifah; Syaikhu Nuris, Muhammad; Suhada, Siti (Universitas Nahdlatul Ulama Kalimantan Timur, 2023)
This study was conducted to find out how the stages of the talk show program production process on the Islamic Center Dakwah Channel in East Kalimantan in presenting communication messages and how the strategy for planning and presenting the talk show program production on the Dakwah Islamic Center East Kalimantan Channel in presenting communication messages. This research was descriptive and qualitative using analytical techniques from Miles and Huberman. The research location was the East Kalimantan Islamic Da'wah Channel Television Station. Data collection was done by observing, interviewing, and documentation. Informants in this study were three people consisting of producers as well as program directors, presenters, and Master Control Room (MCR) of the Umpat Betakun TV Channel Dakwah Islamic Center East Kalimantan. The results of the study were shown the production stage carried out in the Umpat Betakun program went through three stages, namely Pre- Production which was the initial stage of the entire series of production processes for the Umpat Betakun program, Production was the ongoing stage of production for the Umpat Betakun program, Post-Production was the final stage in the form of evaluation between event directors and production team. As the program planning strategies, such as determining themes, determining broadcast times, and utilizing social media to promote the program and in the presentation strategy, the Umpat Betakun program was made as relaxed as possible between the resource person and the presenter. The talk show is presented with a deep interactive feel and provides opportunities for viewers at home or the public to participate in interactive dialogue through comments on YouTube live broadcasts or sending messages via WhatsApp chat.